ROS-dependent signal transduction. (April 2015) - Reczek, Colleen R; Chandel, Navdeep S
Abstract : Reactive oxygen species (ROS) are no longer viewed as just a toxic by-product of mitochondrial respiration, but are now appreciated for their role in regulating a myriad of cellular signaling pathways. H2 O2, a type of ROS, is a signaling molecule that confers target specificity through thiol oxidation. Although redox-dependent signaling has been implicated in numerous cellular processes, the mechanism by which the ROS signal is transmitted to its target protein in the face of highly reactive and abundant antioxidants is not fully understood. In this review of redox-signaling biology, we discuss the possible mechanisms for H2 O2 -dependent signal transduction.